1988
DOI: 10.2165/00003088-198814030-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Plasma Protein Binding on the Fetal/Maternal Distribution of Drugs at Steady-State

Abstract: Maternal and fetal plasma differ in their concentrations of the important drug binding plasma proteins, albumin and alpha 1-acid glycoprotein, with albumin being slightly more concentrated in fetal plasma, and alpha 1-acid glycoprotein being only 37% of the maternal concentration at term. In general, these differences relate linearly to the bound to free concentration ratio of drugs associated with these proteins. Although only the free concentration is generally considered to be the pharmacologically active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 80 publications
2
62
2
Order By: Relevance
“…Plasma protein binding influences the interpretation of data relating to the transplacental transfer and foetal/maternal distribution of drugs (Hill & Abramson, 1988). Previous studies (Hamar & Levy, 1980;Thomas et al, 1976;Tucker et al, 1970) have shown that only free drugs equilibrate between maternal and cord plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma protein binding influences the interpretation of data relating to the transplacental transfer and foetal/maternal distribution of drugs (Hill & Abramson, 1988). Previous studies (Hamar & Levy, 1980;Thomas et al, 1976;Tucker et al, 1970) have shown that only free drugs equilibrate between maternal and cord plasma.…”
Section: Discussionmentioning
confidence: 99%
“…First, maternal and fetal difference in the extent of drug binding to plasma proteins is a key determinant of drug availability, 53 and this is particularly important for SRIs that are highly protein 18,19 Second, the magnitude of drug clearance in the fetus is important, particularly with chronic drug dosing that results in steady-state plasma drug concentrations, as is typical for SRI drug therapy. Further, fetal drug clearance can be divided into placental (that is, fetal-to-maternal drug transfer) and nonplacental clearance, including hepatic drug metabolism and renal drug excretion.…”
Section: Fetal Contributions To Ssri Metabolism and Dispositionmentioning
confidence: 99%
“…For drugs bound mainly to al-acid glycoprotein (AAG), binding in foetal serum is lower than in maternal serum, an observation that has been explained by a lower foetal a,-acid glycoprotein (AAG) concentration [1,2]. Many drugs are used as racemic mixtures, and differences in the serum binding of their enantiomers in adults have been reported [3].…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Therefore we have measured the binding of the isomers of propranolol and verapamil in pairs of maternal and foetal serum samples obtained at delivery; both drugs are bound to AAG and show enantioselective serum binding in adults [4][5][6]. We also determined whether, based on the foetal/maternal AAG concentration ratio, foetal binding of the enantiomers can be predicted from maternal binding data [1]. Protein binding Drug binding in serum was determined by equilibrium dialysis at 370 C as described previously [8].…”
Section: Introduction Methodsmentioning
confidence: 99%